Educator Professional Subjectivities in Gamification: Knowing, Being and Doing - Natalie-Jane Howard; Elizabeth J. Cook (Sagamedia Teknologi Nusantara, 2025)
Gamification has emerged as a prominent innovation in contemporary education, yet its influence on the enactment of educators’ professional subjectivities remains underexplored. As such, little is known about how online gamification applications like Kahoot shape the dynamic ways educators perceive, understand and enact their professional selves within higher education contexts. Adopting a tripartite framework of knowing (epistemological), being (ontological) and doing (praxiological), this qualitative study employed visual-elicitation interviews and remote observations with ten lecturers at a Middle Eastern college. The analysis revealed three key themes shaping educator subjectivities: creating and sharing quiz content; conforming with institutional culture; and infantilizing students with gamified learning. The findings suggest that Kahoot influenced how these educators perceived and performed their professional roles, enabling them to position themselves as creative content developers and aligned institutional practitioners, while also raising concerns about appropriate pedagogical approaches in tertiary contexts. This study demonstrates how gamification applications may actively shape professional subjectivities in higher education, emphasizing how successful gamification requires careful consideration of both institutional support and educator agency. Moreover, the findings offer important implications for professional development, institutional policy, and the thoughtful integration of gamification across diverse cultural contexts in contemporary higher education.